2016
DOI: 10.3201/eid2202.151175
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Hospital-Based Hygiene and Water Treatment Intervention (CHoBI7) to Reduce Cholera

Abstract: This intervention significantly reduced symptomatic Vibrio cholerae infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
159
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(171 citation statements)
references
References 32 publications
12
159
0
Order By: Relevance
“…In our recent randomized controlled trial (RCT) of this intervention where CHoBI7 was compared with the standard message given in Bangladesh to diarrhea patients at discharge on ORS use, we observed a 47% reduction in the incidence of overall cholera infections (symptomatic and asymptomatic), and a significant reduction in symptomatic cholera infections among household members of cholera cases in the intervention compared with the control arm during the 1 week intervention period. 36 These findings demonstrated the effectiveness of the hospital-based CHoBI7 intervention in reducing cholera infections among highly susceptible household members of cholera cases.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In our recent randomized controlled trial (RCT) of this intervention where CHoBI7 was compared with the standard message given in Bangladesh to diarrhea patients at discharge on ORS use, we observed a 47% reduction in the incidence of overall cholera infections (symptomatic and asymptomatic), and a significant reduction in symptomatic cholera infections among household members of cholera cases in the intervention compared with the control arm during the 1 week intervention period. 36 These findings demonstrated the effectiveness of the hospital-based CHoBI7 intervention in reducing cholera infections among highly susceptible household members of cholera cases.…”
Section: Introductionmentioning
confidence: 79%
“…[25][26][27]44 Consistent with this, during the 1-week CHoBI7 intervention period, we observed 55% handwashing with soap events at key times in the intervention arm compared with 8% in the control arm. 36 This high uptake of the promoted behaviors during the week-long CHoBI7 intervention was likely sufficient for households to become habituated with these practices and sustain them over time. Second, the study hardware likely facilitated the promoted behaviors included in the CHoBI7 intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed methods for this intervention and trial are published elsewhere. 19 The intervention arm received chlorine tablets (NaDCC, 33 mg) for water treatment, a Topaz container (sealed drinking water vessel with tap) for safe water storage, and a handwashing station. The control arm received no intervention hardware.…”
Section: Methodsmentioning
confidence: 99%
“…We selected three drinking water vessels: a 16-L locally made plastic bucket with lid, a 10-L aluminum kalshi with no lid (both commonly used in Bangladesh), and a 10-L Topaz ™ (Lion Star Plastic, Jakarta, Indonesia) drinking vessel, used in our Cholera-Hospital-Based Intervention for 7 days (CHoBI7) intervention study. 19 Topaz is a container made of high-quality plastic that can be sealed by a lid that screws on, and has a tap at the bottom to dispense water. This type of container reduces the chances of secondary contamination by the user and prevents evaporation of chlorine.…”
Section: Methodsmentioning
confidence: 99%
“…Hospital-based Hygiene -Researchers found that seven consecutive days of hygiene education given to cholera patients and caretakers had significant disease reduction in an RCT in Bangladesh (George et al 2016). The intervention, Cholera-Hospital-Based-Intervention-for-7-Days (CHoBI7), was held within the hospital and included equipping families with a hygiene kit to facilitate safe drinking water and handwashing.…”
Section: Wash and Health -Outbreak Specific Responsesmentioning
confidence: 99%